Aerial root formation in Oaxacan maize (Zea mays) landraces persists into the adult phase and is minimally affected by soil nitrogen and ambient humidity - Venado, Rafael E.; Wilker, Jennifer; Infante, Valentina; McLimans, Caitlin; Robbins, Fletcher; Phillips, Courtney; Calderón, Claudia Irene; Wallace, Jason G.; Ané, Jean-Michel (Frontiers in Plant Science, 2025)
Maize (Zea mays L.) is the most widely produced crop in the world, and conventional production requires significant amounts of synthetic nitrogen fertilizer, which has negative economic and environmental consequences. Maize landraces from Oaxaca, Mexico, can acquire nitrogen from nitrogen-fixing bacteria that live in a mucilage secreted by aerial nodal roots. The development of these nodal roots is a characteristic traditionally associated with the juvenile vegetative stage of maize plants. However, mature Oaxacan landraces develop many more nodes with aerial roots than commercial maize varieties. Our study shows that Oaxacan landraces develop aerial roots during the juvenile and adult vegetative phases and even during early flowering under greenhouse and field conditions. Surprisingly, the development of these roots was only minimally affected by soil nitrogen and ambient humidity. These findings are an essential first step in developing maize varieties to reduce fertilizer needs in maize production across different environmental conditions.